ADDRESSING THE INEQUALITY OF THEATER EDUCATION IN TEACHER TRAINING INSTITUTIONS - Prusdianto Prusdianto; Andi Sulfana Masri (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
Lembaga Pendidikan Tenaga Kependidikan (LPTK) or The Teacher Training Institutions play an important role in preparing educators at various levels of education, including arts education. However, theater education at LPTK experiences significant disparities compared to music and dance, both in curriculum structure and institutional support. This study explores the inequalities in theater education at LPTK, specifically in Sendratasik Education Study Program at Makassar State University (UNM). Using a descriptive quantitative approach, data were collected through a survey of 147 students, 71 alumni, and 8 lecturers. The results of the study revealed three main challenges: (1) an underdeveloped curriculum, (2) a limited number of lecturers who specialize in theater education, and (3) declining student interest in theater. This study proposes several strategies to address these disparities, including enriching the curriculum with pedagogical-based courses, recruiting more lecturers who specialize in theater education, and increasing student interest through theater festivals and professional collaborations. By addressing this gap, LPTK can create more inclusive and effective theater education, ensuring that prospective theater educators have competencies that are relevant to the dynamic world of education.